Ethics as an Axiology of Science and Disruption AI - Ridhallah, Fauzi; Zalnur, Muhammad; Fithri, Widia (Journal of Islamic Thought and Philosophy, 2026)
This study discusses the role of ethics as an axiology of scientific concepts and technological developments. The development of AI science and technology basically consists of 3 basic concepts, namely ontology, epistemology and axiology. One of the axiological aspects that must be present is ethics. In his study, ethics is the basic reference in the development of science, without ethics, the science and technology developed have no value. The methodology of this study includes analysis of sources and phenomena that occur at this time taken from journals, books, and cases. In the disruption of AI science and technology today, there are still many humans who use today's AI science and technology to behave in deviant ways so as to tarnish the axiological aspects of science itself. The aim of this study is how ethics can be the foundation for the disruption of AI science and technology so that science and technology are not used for negative things.